2015
DOI: 10.1371/journal.pone.0127899
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of CD8+ and CD4+ T Cell Frequencies Specific for EBV LMP1 and LMP2a Using mRNA-Transfected DCs

Abstract: An EBV-specific cellular immune response is associated with the control of EBV-associated malignancies and lymphoproliferative diseases, some of which have been successfully treated by adoptive T cell therapy. Therefore, many methods have been used to measure EBV-specific cellular immune responses. Previous studies have mainly used autologous EBV-transformed B-lymphoblastoid cell lines (B-LCLs), recombinant viral vectors transfected or peptide pulsed dendritic cells (DCs) as stimulators of CD8+ and CD4+ T lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The IFN-γ ELISPOT assay was performed as described previously in literature, with modifications ( 19 ). Briefly, autologous CD8 + T cells (10 6 cells) were serially diluted in complete RPMI and 100 µL of each cell suspension was then transferred into the wells, followed by the addition of 200 µL of aAPC and aAPC-pp65 (10 5 cells) untransfected or transfected with individual HLA-matched single HLA allotype.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IFN-γ ELISPOT assay was performed as described previously in literature, with modifications ( 19 ). Briefly, autologous CD8 + T cells (10 6 cells) were serially diluted in complete RPMI and 100 µL of each cell suspension was then transferred into the wells, followed by the addition of 200 µL of aAPC and aAPC-pp65 (10 5 cells) untransfected or transfected with individual HLA-matched single HLA allotype.…”
Section: Methodsmentioning
confidence: 99%
“…ELISPOT using pp65-transduced CD40-activated B cells has been used for identifying CTL epitopes presented by various HLA allotypes ( 10 ). Epstein–Barr virus (EBV)-specific CD8 + T cell responses can be evaluated using autologous dendritic cells transfected with EBV latent membrane protein 1 and latent membrane protein 2A mRNA ( 19 ). To comprehensively analyze CD8 + T cell responses against the CMV pp65 antigen restricted by a single HLA class I allotype, we conducted ELISPOT assays using an artificial antigen-presenting cell (aAPC) expressing both the pp65 antigen and each HLA class I allotype present in a donor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the persistent antigen presence of EBV-infected B-blasts triggers a robust T cell response that controls the events of reactivation (Hislop et al, 2005 ; Lünemann et al, 2007 ; Lassmann et al, 2011 ). The mechanism may involve LMP1 as it can act on T cells and studies have shown the responses are particularly T H 1 polarized leading to IFN-γ, TNF-α and IL-2 secretion (Sohn et al, 2015 ).…”
Section: Nf-κb In Ms Pathogenesismentioning
confidence: 99%
“…In our previous study, CD8 + and CD4 + T cells responding to LMP1 and LMP2A, respectively, were measured in mRNA-transfected dendritic cells (DCs). As a result, we observed that the LMP1-specific CD4 + T cell response was significantly higher than the LMP2A-specific CD4 + T cell response ( 5 ).…”
Section: Introductionmentioning
confidence: 79%
“…EBV is associated with human malignancies, including Burkitt's lymphoma, Nasopharyngeal carcinoma, Hodgkin’s lymphoma, and lymphoproliferative disorders, in immunocompromised individuals ( 3 ). EBV latency-II Ags such as Epstein-Barr nuclear Ag-1, latent membrane protein 1 (LMP1), and latent membrane protein 2A (LMP2A), are expressed in malignant cells ( 4 5 ). LMP2A mimics the activated B cell receptors (BCR) and inhibits normal signal transduction.…”
Section: Introductionmentioning
confidence: 99%